Implantoprosthetic Rehabilitation by Computer-guided Implant Surgery (M-Guide): Case report - Roko Bjelica; Joško Viskić; Goran Batinjan; Irina Filipović Zore (University of Zagreb. School of Dental Medicine, 2022)
Correct implant positioning poses a major challenge in modern dentistry and mismatch between the planned and final implant position is one of the most common treatment complications. A surgical guide or a template is a ''transmission device'' which enables the implant placement in the intended position as accurate as possible. Case study: A woman aged 60 came into dental office to resolve a single tooth loss in regions 15 and 24. Radiographic analysis and clinical examination showed a lack of transversal space in the regions of implantation. Considering the fact of having a narrow area available for implantation, a computer-guided implant therapy using the M-Guide system was selected. The treatment plan was a prosthetic restoration involving the placement of two implants in areas 15 and 24 and the fabrication of zirconium oxide crowns. After digital planning, a fully guided surgical protocol was performed. Immediately after implantation, a temporary suprastructure and temporary crowns were placed. After a period of osseointegration, a definitive prosthetic restoration was made.